2014
DOI: 10.1101/gad.234468.113
|View full text |Cite
|
Sign up to set email alerts
|

HDAC-regulated myomiRs control BAF60 variant exchange and direct the functional phenotype of fibro-adipogenic progenitors in dystrophic muscles

Abstract: Fibro-adipogenic progenitors (FAPs) are important components of the skeletal muscle regenerative environment. Whether FAPs support muscle regeneration or promote fibro-adipogenic degeneration is emerging as a key determinant in the pathogenesis of muscular diseases, including Duchenne muscular dystrophy (DMD). However, the molecular mechanism that controls FAP lineage commitment and activity is currently unknown. We show here that an HDAC-myomiR-BAF60 variant network regulates the fate of FAPs in dystrophic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(182 citation statements)
references
References 44 publications
3
179
0
Order By: Relevance
“…49 Accordingly, pharmacological treatment with HDAC inhibitors (HDACi) leads to morphological and functional recovery of the dystrophic phenotype in mdx mice. [50][51][52][53] Still a stage-dependent beneficial effect of HDACi treatment has been reported being HDACi efficacy restricted to early stages of the disease. 52,54 Interestingly, the refractoriness to HDACi treatment coincides with the premature block of autophagy reported in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Accordingly, pharmacological treatment with HDAC inhibitors (HDACi) leads to morphological and functional recovery of the dystrophic phenotype in mdx mice. [50][51][52][53] Still a stage-dependent beneficial effect of HDACi treatment has been reported being HDACi efficacy restricted to early stages of the disease. 52,54 Interestingly, the refractoriness to HDACi treatment coincides with the premature block of autophagy reported in this work.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] Still a stage-dependent beneficial effect of HDACi treatment has been reported being HDACi efficacy restricted to early stages of the disease. 52,54 Interestingly, the refractoriness to HDACi treatment coincides with the premature block of autophagy reported in this work. Recent evidence underscores a role of HDACi in inducing autophagy 55,56 by directly regulating LC3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FAPs from dystrophic muscles at advanced stage of disease are resistant to the beneficial effects of HDACi, accounting for the stage-specific effect of HDACi previously observed by Mozzetta et al [9] Genome-wide studies of chromatin accessibility showed that at early stages of the disease, HDACi promote an extensive chromatin remodeling, which was not observed at late stage of the disease. [14] This finding indicates that pharmacological interventions that target FAPs could be used to promote compensatory regeneration, while preventing fibroadipogenic degeneration of DMD muscles. It also suggests that FAPs of dystrophic muscles at late stages of DMD progression might acquire a chromatin conformation that confers resistance to treatments that are…”
Section: Hdac Inhibitors For Muscular Dystrophies: Progress and Prospmentioning
confidence: 99%
“…MyomiRs in turn target two alternative BAF60 variants -BAF60 A and B -that when incorporated into the Switch/Sucrose NonFermentable (SWI/SNF) chromatin-remodeling complex would otherwise promote the activation of the fibro-adipogenic program. [14] Thus, HDACi-mediated selection of BAF60 C-based SWI/SNF complex appears to mediate a therapeutic switch of FAP phenotype from pro-fibroadipogenic to pro-myogenic one. Interestingly, FAPs from dystrophic muscles at advanced stage of disease are resistant to the beneficial effects of HDACi, accounting for the stage-specific effect of HDACi previously observed by Mozzetta et al [9] Genome-wide studies of chromatin accessibility showed that at early stages of the disease, HDACi promote an extensive chromatin remodeling, which was not observed at late stage of the disease.…”
Section: Hdac Inhibitors For Muscular Dystrophies: Progress and Prospmentioning
confidence: 99%
See 1 more Smart Citation